The Effect of Ginger Oil–Based Effleurage Massage on the Intensity of Lower Back Pain among Weavers - Putu Diah Maharani; Ni Rai Sintya Agustini; Dwi Prima Hanis Kusumaningtiyas (Discover Health and Medicine, 2026)
Introduction: Lower back pain (LBP) is a common musculoskeletal complaint frequently experienced by individuals engaged in repetitive and prolonged working postures, including weavers. Persistent LBP may cause muscle stiffness and soreness and, if not properly managed, can negatively affect work performance and productivity. Non-pharmacological interventions are increasingly recommended to manage musculoskeletal pain. One such intervention is effleurage massage combined with ginger oil, which is believed to promote muscle relaxation and reduce pain. This study aimed to examine the effect of effleurage massage using ginger oil on lower back pain intensity among members of the Putri Mas weaving group in Batuagung Village. Methods: This study employed a pre-experimental design using a one-group pre-test and post-test approach. The study population consisted of weavers from the Putri Mas Group in Batuagung Village. A total of 53 respondents were selected using purposive sampling. The intervention involved applying effleurage massage with ginger oil to the lower back for 15 minutes per session. Pain intensity before and after the intervention was assessed using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon Signed Rank Test. Results: Prior to the intervention, all participants reported experiencing lower back pain, with most classified as having moderate pain intensity. Following the intervention, all participants demonstrated a reduction in pain intensity, with the majority reporting mild pain. Statistical analysis using the Wilcoxon Signed Rank Test revealed a Z value of −6.783 and a p-value < 0.001, indicating a statistically significant difference before and after the intervention (p < 0.05). Thus, the null hypothesis was rejected. Conclusion: The findings indicate that effleurage massage using ginger oil is effective in reducing lower back pain intensity among weavers. Future research is recommended to employ a controlled experimental design and include a larger sample size across different weaving groups to strengthen the generalizability of the results.